APPLICATION OF FACEBOOK TO ENGLISH TEACHING AND LEARNING: CASE OF MBEYA CITY - Wilfred Madata (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Educators and policymakers have taken notice of the widespread usage of Facebook as an online social network and as an alternative method of teaching and learning. People around the world use Facebook for communication and as an English language teaching technique. When language learners use Facebook, they may come across new vocabulary and grammar rules. Despite the widespread usage of Facebook in education around the world, little research is done on how facilitators and students in Tanzanian secondary schools use it to teach and learn English. This study surveyed the level to which selected ordinary secondary schools in Tanzania apply Facebook to teach and learn English as a second language. It also investigated the awareness of students and language teachers towards the application of Facebook in teaching and learning of English language in their respective schools. The Descriptive research design was applied in data collection. The data was collected from 15 teachers who are teaching the English language and 78 students from three selected ordinary level secondary schools by using structured interview techniques and questionnaires respectively. The stratified purposive random sampling was employed to draw the respondents. Both statistical Packages for the Social Sciences (SPSS), content analysis, and excel techniques employed in analyzing data. The results show that Facebook is not mostly used as a teaching and learning tool in ordinary secondary schools in Tanzania despite the fact that teachers and students make use of it. Furthermore, it found that language learners might acquire new vocabularies and skills such as listening, writing, reading, and speaking through using Facebook.